Analysis Effect of Service Quality, Educational Facilities, and Method of Learning, Student Satisfaction and Loyalty to Students - Studies in the University of Widyatama Bandung - Dora, Yenny Maya (European Journal of Social Science Education and Research, 2018)
This study aimed to analyze the effect of service quality, education facilities, and teaching methods in conjunction with student satisfaction and loyalty Widyatama University students. The research was conducted by survey method, the data obtained by distributing questionnaires to students. The study population was a student Of the Faculty of Business and Management, University of Widyatama. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. From these results it can be concluded that the loyalty of the students affected by the quality of the service through student satisfaction. Loyalty affected by the Educational Facilities through student satisfaction. And loyalty is also influenced by learning through student satisfaction.